GAMBARAN DISIPLIN KERJA DAN KOMPENSASI BERPENGARUH PADA KEPUASAN KERJA KARYAWAN PDAM TIRTA BERKAH KABUPATEN - Afriyady, Moch Andry; Nuryanti, B Lena (Business Education Program of Universitas Pendidikan Indonesia, 2016)
Purpose: This study is to obtain findings regarding: Overview of labor discipline in the Regional Water Company PDAM Tirta Blessing Pandeglang, description of compensation for employees of PDAM Tirta Blessing Pandeglang, description of employee job satisfaction PDAM Tirta Blessing Pandeglang, amount of influence work discipline on employee job satisfaction Regional Water Company PDAM Tirta Blessing Pandeglang amount of influence compensation to employee satisfaction Regional Water Company PDAM Tirta Blessing Pandeglang amount of influence the discipline of work and compensation to employee satisfaction Local Company Blessing water PDAM Tirta PandeglangDesign/methodology/approach: Based on the level of explanation and research fields, then this type of research is descriptive and verification. Meanwhile, According Sugiyono (2013: 11)